1995
DOI: 10.1002/ajh.2830500105
|View full text |Cite
|
Sign up to set email alerts
|

Use of recombinant hirudin as antithrombotic treatment in patients with heparin‐induced thrombocytopenia

Abstract: Heparin-induced thrombocytopenia is a rare but severe complication of heparin therapy that can result in severe venous or arterial thromboembolic events and whose treatment remains partially unanswered. Recombinant hirudin is potentially effective as an antithrombotic treatment in the management of heparin-induced thrombocytopenia, given its potent antithrombin effects without known interaction with platelets. We report the results obtained with intravenous recombinant hirudin (HBW 023) administered on a compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(33 citation statements)
references
References 26 publications
0
30
0
3
Order By: Relevance
“…Two new direct antithrombin drugs, Hirudin and Argatroban, may prove to be efficient and safe in patients with HIT undergoing CPB. Both are short acting, and initial experience is encouraging (Matsuo et al, 1992;Schiele et al, 1995). Unfortunately, we were unable to obtain either of these drugs for our patient.…”
Section: Discussionmentioning
confidence: 93%
“…Two new direct antithrombin drugs, Hirudin and Argatroban, may prove to be efficient and safe in patients with HIT undergoing CPB. Both are short acting, and initial experience is encouraging (Matsuo et al, 1992;Schiele et al, 1995). Unfortunately, we were unable to obtain either of these drugs for our patient.…”
Section: Discussionmentioning
confidence: 93%
“…Lepirudin is a synthetic recombinant form of hirudin derived from yeast. A prospective trial involving 82 patients with HIT showed it to be a safe and effective alternative anticoagulant [15,16]. Two separate studies involving 6 and 20 patients, respectively, on hemodialysis revealed that lepirudin can be used safely as the sole anticoagulant, though close monitoring was required, as lepirudin is renally cleared [17,18].…”
Section: Direct Thrombin Inhibitors (Hirudin Lepirudin Argatroban)mentioning
confidence: 99%
“…Empiric recommendations regarding heparin dosage during coronary angioplasty have been proposed (728,729), but ACT levels after a fixed dose of unfractionated heparin may vary substantially due to differences in body size (730), concomitant use of other medications, including intravenous nitroglycerin (731,732), and in the presence of acute coronary syndromes that increase heparin resistance.…”
Section: Tirofibanmentioning
confidence: 99%